Islam, Peradaban Masa Depan - Abdul Wadud Nafis (Jurnal Al-Hikmah, 2020)
Islam is a universal civilization, a religion of equity not destruction. Islam encourages its followers to believe in their own abilities and not depend on what other people give while prioritizing what is beneficial for them. Islamic civilization will develop if it is able to communicate with the local culture in a selective manner and still adheres to Aswaja (Ahlus sunnah Wal Jamaah) values. If Islam blindly followed the developing culture in the society, both the local and foreign cultures, Islam would lose its identity and the Muslim community would be separated from its cultural roots. The values ​​of Islamic civilization are: Rabbiyah value (the divine values), Insâniyah value ​​(the human value). Wâqi'iyah value ​​(the practical value), Wasathiyah value ​​(the Islamic moderatation value), Tawâzun value ​​(the equilibration value), Tsabât value ​​(the fixity value) and Murûnah value (the flexibility value). The nobleness of Islamic values ​​should not only be a theory, but also needs to be implemented. The deeper the implementation, the more sublime the civilization will be. Human life must be based on the belief that we belong to Allah and to Him we shall return.